Bifuctional indigocarminintercalated NiAl layered double hydroxide: investigation of characteristics for pigment and supercapacitor application - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2020)
In the modern world, one promising direction is the production and use of multifunction compounds. Ni-Al layered double hydroxide is widely used as the active material in supercapacitors. Nickel compounds are also colored and can be used as pigments. The characteristics of bi-functional indigo carmine intercalated Ni-Al (Ni:Al=4:1) hydroxides, synthesized at an equilibrium рН and рН=14 have been studied. The crystal structure of the prepared samples was studied by means of X-ray diffraction analysis and thermogravimetry, pigment characteristics – by measuring and calculating color characteristics in CIELab and XYZ systems, electrochemical characteristics – cyclic voltammetry and galvanostatic charge-discharge cycling. Comparative analysis of the electrochemical characteristics of Ni-Al-indigo carmine and Ni-Al-carbonate hydroxides has been conducted. Using XRD and thermogravimetry analysis methods, it was found that Ni-Al–indigo carmine hydroxide is a layered double hydroxide with the structure of α-Ni(OH)2 with average (synthesis at рН=14 and low (synthesis at equilibrium рН) crystallinity. It was found that synthesized Ni-Al-indigo carmine LDH had color bordering between light and blue (color tone 483–485 nm) with the lightness of 40–50 % and average color purity. It was found that the specific capacity of indigo carmine intercalated Ni-Al LDH (synthesis at рН=14 exceeded that of carbonate intercalated: the maximum specific capacity at full discharge was 1,007 F/g hydroxide and 2,996 F/h Ni, at discharge to 0 В –946 F/g. First, for Ni-Al-indigo carmine LDH, two discharge plateaus were observed, which correspond to the discharge of Ni3+ and indigo carmine